Improved Anti-Tumor Effect of Liposomal Doxorubicin After Targeted Blood-Brain Barrier Disruption by MRI-Guided Focused Ultrasound in Rat Glioma - Treat, Lisa H.; McDannold, Nathan; Zhang, Yongzhi; Vykhodtseva, Natalia; Hynynen, Kullervo (Ultrasound in medicine & biology, 2012)
The blood-brain barrier (BBB) inhibits the entry of the majority of chemotherapeutic agents into the brain. Previous studies have illustrated the feasibility of drug delivery across the BBB using focused ultrasound (FUS) and microbubbles. Here, we investigated the effect of FUS-enhanced delivery of doxorubicin on survival in rats with and 9L gliosarcoma cells inoculated in the brain. Each rat received either: (1) no treatment (control; N = 11), (2) FUS only (N = 9), (3) IV liposomal doxorubicin (DOX only; N = 17), or (4) FUS with concurrent IV injections of liposomal doxorubicin (FUS+DOX; N = 20). Post-treatment by magnetic resonance imaging (MRI) showed that FUS+DOX reduced tumor growth compared with DOX only. Further, we observed a modest but significant increase in median survival time after a single treatment FUS+DOX treatment (p = 0.0007), whereas neither DOX nor FUS had any significant impact on survival on its own. These results suggest that combined ultrasound-mediated BBB disruption may significantly increase the antineoplastic efficacy of liposomal doxorubicin in the brain.